Outcome of Ponseti Casting in Maltreated Clubfeet in Children Up To 5 Years of Age: A Study of 120 Patients - ud Din Zafir, Muhammad Badar; Tariq, Mukhtar Ahmad; Ali, Mazhar; Ahmad, Khadija; Raza, Tauseef; Hussain, Baqir (Journal of Neonatal Surgery, 2025)
Background: CTEV, or clubfoot, is a common congenital deformity which can lead to severe physical and functional limitations if neglected or improperly treated. The Ponseti method involving non-surgical treatment through serial casting, Achilles tendon tenotomy, and bracing has been successfully used on clubfoot patients even when delay to treatment occurs. Methodology: This study evaluates the outcomes of Ponseti casting in 120 children with neglected clubfeet aged five years and younger. Treatment effectiveness was calculated using SPSS 26 software for descriptive and inferential data analysis. Results: The study found that the Ponseti method was effective in 110 out of 120 children, resulting in a 91.6% overall success rate. The results, including age-based treatment success rates and statistical significance. Conclusions: In corrective Ponseti therapy substantial improvements in deformities were noted yielding a 91.6% success rate. Timely interventions combined with strict adherence to off-brace policies significantly influenced successful outcomes